A survey on face emotion recognition and applications - Muthukaruppan, Karthigayan; Mohd Rizon, Mohamed Juhari; Ramachandran, Nagarajan (Association for the Advancement of Modelling and Simulation Techniques in Enterprises (AMSE), 2009)
Link to publisher's homepage at http://www.amse-modeling.org/Periodical_AMSE.html